France - Tomalin, Barry, 1942- (London : Kuperard, 2013)
Culture Smart! France provides essential information on local attitudes, beliefs and behaviour. This concise guide will tell you what to expect and how to behave. This inside knowledge will enable you to avoid embarrassing faux pas, feel confident. It explains how French life and business work and shows you how to fit in as a foreigner. There is practical advice on how to avoid the pitfalls and do things the French way. It takes you through history, festivals, and traditions, the French at home, on the road, in the restaurant, and at work. Above all, it shows you how the French communicate, and how best to get along with this sometimes frustrating yet charming and brilliant people.
Land and people -- Values and attitudes -- Customs and traditions -- Making friends -- The French at home -- Time out -- Traveling -- Business briefing -- Communicating.
Includes bibliographical references (page 165) and index.
Keywords: Etiquette -- France -- Handbooks, manuals, etc; National characteristics, French -- Handbooks, manuals, etc; Visitors, Foreign -- France -- Life skills guides; Manners and customs